Conjugal Relationships in Chinese Culture
XVIII, 179 p. 17 illus., 1 illus. in color.
Keywords: This book reviews the presentation of conjugal relationships in Chinese culture and their perception in the West. It explores the ways in which the act of marriage is represented/misrepresented in different literary genres, as well as in cultural adaptations. It looks at the gendered characteristics at play that affect conjugal relationships in Chinese societal practices more widely. It also distinguishes between the essential features that give rise to nuptial arrangements from the Chinese perspective, looking at what in which Sino and/or Western mentalities differ in terms of notions of autonomy in marriage. It excavates the extent to which marriage is constituted in forms of transaction between female and male bodies and asks under what circumstances wedding ceremonies constitute archetypal or counter-archetypal notions in pre-modern and modern society. Authors cover a range of fascinating cultural topics, such as posthumous marriage (necrogamy) as an ancient and popular folk culture from the perspective of Confucian ideology, as well as looking at marriage from ancient to present times, duty and rights in conjugal relations, inter-racial and inter-cultural marriage, widowhood in Confucian ideology, issues of legitimacy in marriage and concubinage, the taboos surrounding divorce and re-marriage, and conjugal violence. The book serves to revisit the cultural connections between marriage and various art forms, including literature, film, theatre, and other adaptations. It is a rich intellectual resource for scholars and students researching the historical roots, cultural interpretations, and evolving aspects of marriage as shown in literature, art, and culture.